Infection with hepatitis C virus as a cause of nervous system disorders - Krystian Ślusarz; Patrycja Łanowy; Weronika Pyka; Bartosz Bijak; Miłosz Bichalski; Jakub Dzindzio; Jerzy Jaroszewicz (Kazimierz Wielki University, 2019)
Hepatitis C is a disease caused by hepatitis C virus (HCV), which prevalence may reach over 5% in some countries. Untreated infection may lead to death due to cirrhosis or hepatocellular carcinoma. Almost 80% of infected patients occurs as asymptomatic. Symptoms of hepatitis C may include jaundice, nausea, vomiting, fever or muscle and joint pains. Even half of the patients experience nervous system disorders, due to the affinity of some types of HCV to nerve cells. It is also estimated that up to 30% of patients with chronic hepatitis C will develop cirrhosis within 25-30 years. Currently, the vast majority of infected patients can be cured thanks to the introduction of direct-acting antivirals (DAAs).